2006
DOI: 10.1176/ajp.2006.163.10.1826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-HT 1A Receptor Gene Polymorphism on Negative and Depressive Symptom Response to Antipsychotic Treatment of Drug-Naive Psychotic Patients

Abstract: These findings identify an important genetic factor predicting much of the response in negative and depressive symptoms to antipsychotic drug treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 12 publications
(9 reference statements)
2
43
1
1
Order By: Relevance
“…Interestingly, a report shows that the CC-genotype also confers a better response to transcranial magnetic stimulation [142], suggesting that modulation of the 5-HT1A receptor may also participate in treatments that target cortical processes, perhaps via induced expression of the 5-HT1A receptor in cortex and amygdala [143]. The GG-genotype has also been associated with weaker negative symptom improvement in schizophrenia patients treated with atypical antipsychotics [144,145]. Taken together these studies indicate that the G-allele, which is associated with increased 5-HT1A autoreceptor levels, also associates with reduced responses to therapies that modify the 5-HT system.…”
Section: -Ht1a Promoter Polymorphisms and Mental Illnessmentioning
confidence: 99%
“…Interestingly, a report shows that the CC-genotype also confers a better response to transcranial magnetic stimulation [142], suggesting that modulation of the 5-HT1A receptor may also participate in treatments that target cortical processes, perhaps via induced expression of the 5-HT1A receptor in cortex and amygdala [143]. The GG-genotype has also been associated with weaker negative symptom improvement in schizophrenia patients treated with atypical antipsychotics [144,145]. Taken together these studies indicate that the G-allele, which is associated with increased 5-HT1A autoreceptor levels, also associates with reduced responses to therapies that modify the 5-HT system.…”
Section: -Ht1a Promoter Polymorphisms and Mental Illnessmentioning
confidence: 99%
“…A recent study provides support for this theory by reporting association between a 5-HT1A -1019-C/ G polymorphism and antipsychotics improvement of negative symptoms. 115 Further evidence exists of the likely involvement of other serotonin receptors in antipsychotic activity (for example, 5-HT 3A , 5-HT 3B , 5-HT 5A and 5-HT 7 ). However, few genetic studies have attempted to confirm this hypothesis 133,134 and no significant association with antipsychotic response has been reported to date.…”
Section: Pharmacodynamic Factorsmentioning
confidence: 99%
“…We therefore assessed whether the schizophrenia susceptibility gene ZNF804A has a pharmacogenetic importance. Since previous studies with monoamine system genes have shown that a pharmacogenetic role of a given gene may be primarily restricted to the positive or negative symptom response [8,11,14], we queried whether the disease-associated variant of ZNF804A exerts an influence on positive or negative schizophrenia symptoms.…”
Section: Introductionmentioning
confidence: 99%